Shanghai Rising: Health Improvements as Measured by Avoidable Mortality since 2000 - Michael K. Gusmano; Victor G. Rodwin; Chunfang Wang; Daniel Weisz; Li Luo; Fu Hua (Kerman University of Medical Sciences, 2015)
Over the past two decades, Shanghai, the largest megacity in China, has been coping with unprecedented growth of its economy and population while overcoming previous underinvestment in the health system by the central and local governments. We study the evolution of Shanghai's healthcare system by analyzing "Avoidable Mortality" (AM) - deaths amenable to public health and healthcare interventions, as previously defined in the literature. Based on analysis of mortality data, by cause of death, from the Shanghai Municipal Center for Disease Control and Prevention, we analyze trends over the period 2000-10 and compare Shanghai's experience to other mega-city regions - New York, London and Paris. Population health status attributable to public health and healthcare interventions improved dramatically for Shanghai's population with permanent residency status. The age-adjusted rate of AM, per 1,000 population, dropped from 0.72 to 0.50. The rate of decrease in age-adjusted AM in Shanghai (30%) was comparable to New York City (30%) and Paris (25%), but lower than London (42%). Shanghai's establishment of the Municipal Center for Disease Control and Prevention and its upgrading of public health and health services are likely to have contributed to the large decrease in the number and rate of avoidable deaths, which suggests that investments in public health infrastructure and increasing access to health services in megacities - both in China and worldwide - can produce significant mortality declines. Future analysis in Shanghai should investigate inequalities in avoidable deaths and the extent to which these gains have benefitted the significant population of urban migrants who do not have permanent residency status.